2020
DOI: 10.1097/corr.0000000000001577
|View full text |Cite
|
Sign up to set email alerts
|

Are Patient Expectations and Illness Perception Associated with Patient-reported Outcomes from Surgical Decompression in de Quervain’s Tenosynovitis?

Abstract: Background Psychological factors such as depression, pain catastrophizing, kinesiophobia, pain anxiety, and more negative illness perceptions are associated with worse pain and function in patients at the start of treatment for de Quervain’s tenosynovitis. Longitudinal studies have found symptoms of depression and pain catastrophizing at baseline were associated with worse pain after treatment. It is important to study patients opting for surgery for their condition because patients should choose s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 30 publications
2
21
0
Order By: Relevance
“…In contrast to pain catastrophising, higher treatment expectations were independently associated with a better 1-year outcome. This is in line with a previous study on the surgical outcome of Quervain’s disease [ 33 ]. Interestingly, the mean improvement during the first year after surgery -although with a higher level of pain and dysfunction at intake- did not seem to differ based on pain catastrophising or anxiety and depression.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In contrast to pain catastrophising, higher treatment expectations were independently associated with a better 1-year outcome. This is in line with a previous study on the surgical outcome of Quervain’s disease [ 33 ]. Interestingly, the mean improvement during the first year after surgery -although with a higher level of pain and dysfunction at intake- did not seem to differ based on pain catastrophising or anxiety and depression.…”
Section: Discussionsupporting
confidence: 93%
“…Similar to other studies, PCS and PHQ scores were added simultaneously but separately from B-IPQ since pain catastrophising and psychological distress have been studied more extensively [ 10 , 12 , 13 ]. Outcome expectations were only evaluated in the outcome models (model 2) [ 33 ]. The variable treatment was added in the models as an instrumental variable for diagnosis/pathology.…”
Section: Methodsmentioning
confidence: 99%
“…It would therefore be interesting to examine to what extent the clinical staging of the disease contributes to postoperative outcomes and to compare these results with outcomes following conservative management. Furthermore, investigators have also demonstrated that treatment expectations and psychological factors play an important role in postoperative outcomes following surgical decompression of carpal tunnel syndrome (Sun et al., 2021) and De Quervain tenosynovitis (Blackburn et al., 2021). Future studies may examine other factors contributing to postoperative pain and hand function.…”
Section: Discussionmentioning
confidence: 99%
“…However, another factor that could possibly contribute to this difference is treatment expectation, as prior studies found that a higher treatment expectation is associated with better outcomes following carpal tunnel release 40 and surgical decompression of de Quervain tenosynovitis. 41 Because we were primarily interested in the change in functional outcomes in a representative sample of patients undergoing trigger finger release, we did not adjust for covariates in this study. Future studies should investigate factors contributing to this variability in outcomes.…”
Section: Ementioning
confidence: 99%